Highly compact CsPbBr3 perovskite thin films decorated by ZnO nanoparticles for enhanced random lasing - Li, Cunlong; Zang, Zhigang; Han, Ceng; Hu, Zhiping; Tang, Xiaosheng; Du, Juan; Leng, Yuxin; Sun, Kuan (Nano energy, 2017)
Inorganic cesium lead halide perovskites (CsPbX3, X = Cl, Br, I) have attracted enormous attention as a novel optoelectronic material with enhanced stability. However, the perovskite CsPbX3 thin films fabricated by one-step spin-coating method contain the defects of voids or pinholes, seriously affecting their amplified spontaneous emission (ASE) or lasing performance. To solve this issue, herein, we demonstrate that by simply introducing ZnO nanoparticles (NPs) into the CsPbBr3 precursor solution, the CsPbBr3:ZnO films synthesized by one-step spin-coating method exhibit enhanced crystallization, improved photoluminescence (PL) intensity and prolonged lifetime. Introducing the ZnO NPs can provide an effective route for CsPbBr3 nucleation during the spin-coating and annealing process, contributing to compact and smooth thin films with no obviously large voids or pinholes. Under the one-photon (400nm) and two-photon (800nm) femtosecond laser excitation, the ASE of CsPbBr3 and CsPbBr3:ZnO films have been investigated at room temperature, respectively. After the film compactness, surface smoothness and crystal size are modified by the ZnO additive, both the emission efficiency and the ASE threshold of the CsPbBr3:ZnO films have been improved in comparison with the pure CsPbBr3 films. [Display omitted] •Efficient reduction of large voids or pinholes in CsPbBr3 films using ZnO NPs.•CsPbBr3:ZnO films exhibit improved PL intensity and prolonged lifetime.•ASE emission efficiency and ASE threshold of CsPbBr3:ZnO films are improved.